The Effectiveness of Abdominal Stretching Exercises and Dysmenorrhea Gymnastics Against Dysmenorrhea Pain Intensity in Adolescent Girls: Literature Review - Septi Prastiwi; Nur Yeny Hidajaturrokhmah; Suci Anggraeni (PT. Griya Eka Sejahtera, 2021)
Background: Abdominal pain during menstruation (dysmenorrhea) that is felt by every woman is different, some are slightly disturbed but some are so disturbed that they cannot carry out daily activities and make them have to rest and even have to be absent from school or work. This study aimed to explore the differences between abdominal stretching exercises and dysmenorrhea exercises to reduce dysmenorrhea in adolescent girls. Method: the researcher used a literature review design. This literature study uses two databases (Proquest & Google Scholar) with the majority of the research design using quasi-experimental, randomized control, case-control, cross-sectional, qualitative studies, literature/systematic reviews. Picos is used to select studies which include, journals of the last ten years and in both English and Indonesian languages, titles, and abstracts. With a total of 11 journals identified. Results: Abdominal stretching exercises can be done anywhere and anytime so it is not difficult for teenagers who want to do the exercises. Conclusion: This exercise is also very suitable to be applied to teenagers who have a high desire for motion, where this exercise if done regularly can also burn calories which can help shape the body.